Role of Ultrasound-Based Therapies in Cardiovascular Diseases - Amit Bansal, MBBS, PGDip, MPhil, GCert; Bernard Bulwer, MD; Ricarda von Krüchten, Priv.-Doz., Dr. M.; Jagkirat Singh, MD; Rajan Rehan, MBBS, MPH; Ata Doost, MD, MPhil (Structural Heart)
Cardiovascular diseases (CVDs) remain the leading cause of morbidity and mortality globally, placing an immense burden on health care costs worldwide. The emergence of therapeutic ultrasound-based therapies in the CVD management represents a promising innovative strategy beyond current established approaches. This paper explores three distinct modalities of ultrasound-based therapies—high-intensity focused ultrasound, extracorporeal shock wave therapy, and low-intensity pulsed ultrasound—each characterized by unique acoustic parameters and mechanisms of action tailored to specific therapeutic outcomes. High-intensity focused ultrasound was shown to be beneficial as an adjunct in the treatment of myocardial infarction and arrhythmias. It has also been investigated for the in vivo treatment of resistant hypertension, symptomatic aortic valve stenosis, arterial stenosis, tumors, hypertrophic cardiomyopathy, and external cardiac pacing. Extracorporeal shock wave therapy was shown to be beneficial in the treatment of chronic refractory angina pectoris, while low-intensity pulsed ultrasound was shown to be beneficial in dissolving blood clots and improving blood flow in the treatment of acute pulmonary embolism, despite its association with an increased risk of bleeding. Ultrasound-based therapies are, therefore, a potential adjunct and comparatively safe adjuncts for managing challenging CVD cases. Further investigations are essential to validate their long-term effectiveness and safety, particularly for high-risk individuals susceptible to postprocedural complications.